Improving Students' Digital Literacy Skills Through the Use of Online Learning Resources Assisted by Collaborative Discussions - Rossy Alivia Rozana; Ahmad Zaki Emyus; Gandung Wirawan (Postgraduate, University of Mataram, 2025)
This study aims to improve students’ digital literacy skills through the utilization of online learning resources combined with collaborative discussions. The research employed Classroom Action Research (CAR) with two cycles involving 32 eighth-grade students of MTsN 2 Jember, divided into 16 small groups. Each group carried out structured discussions with specific role distribution, namely information seeker, information evaluator, recorder, and presenter, so that each member had a clear responsibility. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively. The findings revealed a significant improvement in four indicators of digital literacy. The ability to access digital information increased from 66% in the first cycle to 87% in the second cycle; the ability to evaluate information rose from 29% to 52%; ethical use of information improved from 31% to 60%; and the ability to create digital content increased from 43% to 72%. These results demonstrate that a learning strategy based on online learning resources combined with structured group discussions can foster students to become more critical, ethical, and creative in utilizing digital technology. Therefore, this model is relevant to be applied in developing students’ digital literacy skills while preparing them to face the challenges of the 21st century.